Dickkopf-1: A suitable target for the management of myeloma bone disease - Gavriatopoulou, M.; Dimopoulos, M.-A.; Christoulas, D.; Migkou, M.; Iakovaki, M.; Gkotzamanidou, M.; Terpos, E. (Expert Opinion on Therapeutic Targets, 2009)
Bone disease remains a major problem in the management of patients with multiple myeloma (MM) and is characterized by the presence of lytic lesions due to increased osteoclastic activity and reduced osteoblast function. Wingless-type and integrase 1 (Wnt)/β-catenin signaling is a central pathway for bone development and homeostasis. Dickkopf-1 (Dkk-1) is a soluble inhibitor of Wnt, which disrupts osteoblast differentiation and action. Dkk-1 is produced by myeloma cells and overexpressed in myeloma microenvironment of patients with extensive bone disease. In addition to its direct inhibitory effect of Dkk-1 on osteoblasts, Dkk-1 disrupts the Wnt3a-regulated osteoprotegerin and receptor activator of NF-κB ligand (RANKL) expression in osteoblasts and thus it indirectly enhances osteoclast function in MM. Dkk-1 serum and bone marrow plasma levels are increased in MM patients and correlated with advanced International Staging System stage and presence of osteolytic lesions. Preclinical studies in mouse myeloma models showed that targeting Dkk-1 with neutralizing anti-Dkk-1 antibodies resulted in increased numbers of osteoblasts, reduced numbers of multinucleated osteoclasts and increased bone volume. The bone anabolic effect of anti-Dkk-1 may also be associated with reduced myeloma burden. These data show that Dkk-1 has a pivotal role in bone health and disease and is a novel target for the management of myeloma patients with lytic bone disease. © 2009 Informa UK Ltd. All rights reserved.
Keywords: Bone disease; Dickkopf-1; multiple myeloma; Treatment; Wnt signaling